DRUG ADDICTION AS A FORM OF DEVIANT BEHAVIOR - Kholova Mohikul Shavkatovna; Kadirova Mahira Mirzaboy qizi (Research Focus International Scientific Journal, 2025)
This article highlights the negative impact of drug addiction on social life, the importance of studying it as a form of deviant behavior. The causes of drug addiction, its negative impact on the minds of young people , and the role of education and family in preventing it are analyzed. Modern psychological and pedagogical solutions to the problem are considered .